The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s42452-020-3030-7
|View full text |Cite
|
Sign up to set email alerts
|

Screening for antioxidant activity of vegetable and fruit by-products and evaluating the ability of coffee sediment to preserve fish meal

Abstract: In this study, we collected and prepared ethanol extracts from 30 vegetable and fruit by-products and screened for antioxidant activities using three methods, including determination of total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl free radical scavenging assay (DPPH assay), and ferric reducing/antioxidant power assay (FRAP assay). The coffee sediment (TN-16) and ginger peel extract (TN-17) showed vigorous activities and higher than those of other samples (p < 0.05). The TPC in TN-16 and TN-17 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The radical scavenging activity of RGP, DGP and GPE compared to standard substances AA and BHT was determined by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay [ 38 ]. To prepare the ethanolic extracts of RGP and DGP, a quantity of each ground sample that provided 1 g of dry substance (d.s.)…”
Section: Methodsmentioning
confidence: 99%
“…The radical scavenging activity of RGP, DGP and GPE compared to standard substances AA and BHT was determined by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay [ 38 ]. To prepare the ethanolic extracts of RGP and DGP, a quantity of each ground sample that provided 1 g of dry substance (d.s.)…”
Section: Methodsmentioning
confidence: 99%
“…Another study on the metabolomic profiling and antioxidant activities of Hyphaene thebaica found that the fruit exhibited antioxidant activities (Taha et al, 2020). A study by Thi et al (2020) on the screening for antioxidant activity of vegetable and fruit by-products found that most samples had weak antioxidant activity, and the effect of antioxidants on DPPH radical scavenging was due to their hydrogen donating ability (Thi et al, 2020). Based on the comparison with previous studies, it is evident that the current study aligns with the broader research landscape on antioxidant activities of fruits and their extracts.…”
Section: Discussionmentioning
confidence: 99%
“…They are rich in bioactive compounds, which can be utilized as novel, low-cost natural sources of antioxidants, antimicrobials, dietary fiber, enzymes, and food additives through different methods of extraction, purification, and fermentation ( Gowe, 2015 ; Kodagoda and Marapana, 2017 ). In a previous study, an ethanol extract of Coffea arabica sediment proved to be one of the most efficient extracts in antioxidant activity and inhibiting tyrosinase ( Hue et al, 2020 ), so it was studied further in this research. This study aimed to examine antioxidant activity and tyrosinase inhibition of an ethanol extract from Coffea arabica sediment and its various fractions.…”
Section: Introductionmentioning
confidence: 99%